2007
DOI: 10.1002/dc.20459
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphology of a solitary left chest wall mass: An unusual presentation from unknown primary hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) may present in various ways, but only very rarely with symptoms of distant metastases or evolve from ectopic liver tissue. This report describes a case of a 62-year-old white man who was admitted for hemoptysis and a large left chest wall mass that was growing for about a year. The patient underwent Fine-needle aspiration (FNA) of the mass that revealed poorly differentiated large-cell carcinoma. A lung primary was suspected initially; however, further workup of this patient show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…More than 80% of the tumor cells were positive for cytokeratin on flow cytometry, which made the diagnosis of myeloma even less likely. While the FNAB findings of occult HCC presenting as nonhepatic masses in the parotid gland, soft tissue and orbit [20][21][22] have been previously reported, its expression of CD138 by flow and IHC has to our knowledge not been described in the cytology literature. Our case highlights the fact that while ancillary studies may be important for diagnosis, thorough clinical information, imaging studies, and a high index of suspicion are also paramount to accurate diagnosis.…”
Section: Discussionmentioning
confidence: 83%
“…More than 80% of the tumor cells were positive for cytokeratin on flow cytometry, which made the diagnosis of myeloma even less likely. While the FNAB findings of occult HCC presenting as nonhepatic masses in the parotid gland, soft tissue and orbit [20][21][22] have been previously reported, its expression of CD138 by flow and IHC has to our knowledge not been described in the cytology literature. Our case highlights the fact that while ancillary studies may be important for diagnosis, thorough clinical information, imaging studies, and a high index of suspicion are also paramount to accurate diagnosis.…”
Section: Discussionmentioning
confidence: 83%
“…ROSE is helpful to communicate with the endoscopist about placement of the needle. From our literature review, while FNA of presumed ectopic liver within the thorax has been reported,[12] ours is the first report of perigastric ectopic liver diagnosed by FNA.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to confirming the presence of hepatic tissue, it was also useful to exclude the possibility of hepatocellular carcinoma, which has been reported in ectopic liver. [9101112] This needle is new to the US market. One pilot study on this device currently in press was performed at our institution and showed that the device performs very well when compared to a standard EUS-FNA needle in terms of yield and reduced number of passes.…”
Section: Discussionmentioning
confidence: 99%
“…Literature reports seven such cases, of which one was diagnosed on cytology. [2][3][4][6][7][8][9] Most of these cases had metastatic HCC from a clinically and radiologically unrecognized liver mass. In the present case, USG revealed a lesion in the right lobe of liver.…”
Section: Discussionmentioning
confidence: 99%
“…The described case presented solely with an isolated chest wall swelling, diagnosed on FNAC. Literature reports seven such cases, of which one was diagnosed on cytology 2–4,6–9 . Most of these cases had metastatic HCC from a clinically and radiologically unrecognized liver mass.…”
Section: Discussionmentioning
confidence: 99%